Decomposing value chains within Swedish multinationals - Kent Eliasson; Pär Hansson; Markus Lindvert (Örebro University School of Business, 2018)
Multinational enterprises (MNE) have been highly instrumental in the processes leading to the increased fragmentation of production within global value chains. We examine the relationship between relative demands for skills, non-routine or non-offshorable tasks in Swedish MNE parents (onshore) and their employment shares in affiliates abroad (offshore), as well as the impact on relative demand in Swedish enterprises at home when establishing an affiliate abroad. The period of study is 2001 to 2013, a period of expansion for Swedish MNEs, particularly in low-income countries such as China. Our instrumental variable estimates suggest that there is a causal relationship of increased employment shares in affiliates abroad (offshore) on higher relative demand for skills and non-routine tasks in the parents at home (onshore) and that the impact of such offshore employment changes onshore is non-negligible. Furthermore, we estimate the relationships between absolute employment onshore (skilled and less-skilled labor) and employment in affiliates offshore (high- and low-income countries). Increased employment in affiliates in lowincome countries is negatively related to the employment of less-skilled workers in manufacturing MNE parents (substitute), whereas increased employment in affiliates in high-income countries is positively related to the employment of both skilled and lessskilled workers in service at MNE parents (complement).
Keywords: F14; F16; F23; J23; J24; 330; multinational enterprises; relative labor demand; offshoring; skill upgrading; non-routine; offshorable tasks